Short-Chained Anthracene Strapped Porphyrins and their Endoperoxides - Senge, Mathias (My University, 2020)
The syntheses of short‐chained anthracene‐strapped porphyrins and their Zn(II)complexes are reported. The key synthetic step is a [2+2] condensation between a dipyrromethane and an anthracene bisaldehyde, 2,2'‐((anthracene‐9,10‐diylbis(methylene))bis(oxy))dibenzaldehyde. Following exposure to white light, self‐sensitized singlet oxygen and the anthracene moieties underwent [4+2] cycloaddition reactions to yield the corresponding endoperoxides. 1H NMR studies demonstrate that the endoperoxide readily formed in [D]chloroform and decayed at 85 °C. X‐ray crystallography and absorption spectroscopy were used to confirm macrocyclic distortion in the parent strapped porphyrins and endoperoxides. Additionally, X‐ray crystallography indicated that endoperoxide formation occurred exclusively on the outside face of the anthracene moiety
Keywords: porphyrins.; absorption spectroscopy; X‐ray crystallography; porphyrins.; absorption spectroscopy; X‐ray crystallography